Phytochemical Analysis and Antifungal Potentiating Activity of Extracts from Loquat (Eriobotrya japonica) against Cryptococcus neoformans Clinical Isolates - Borel Ndezo Bisso; Prudence Ngalula Kayoka-Kabongo; Roland Tchuenteu Tchuenguem; Jean Paul Dzoyem (Hindawi Limited, 2022)
Eriobotrya japonica (loquat) has been used in African traditional medicine with numerous beneficial health effects. The extracts from loquat contain several bioactive compounds with a plethora of pharmacological properties. However, a scientific study on the activity against the aetiological agent of cryptococcosis has not yet been reported. Therefore, this study aimed to investigate the antifungal potential of various extracts from Eriobotrya japonica against clinical isolates of Cryptococcus neoformans. Quantitative and qualitative phytochemical analyses of extracts were made by following standard procedures. The broth microdilution method and the checkerboard methods were used to determine the antifungal activity and the combination of extracts with antifungals drugs. The methanol extract of seeds and the hexane extract of leaves exhibited the best significant antifungal activity with MIC values of 32 µg/mL. Furthermore, the combination of both extracts with nystatin and clotrimazole showed synergistic interactions with a 32-fold reduction in the MIC values of nystatin. Our findings indicate that Eriobotrya japonica extracts are a potential source of new antifungals that could be developed for use in the treatment of cryptococcosis. The anticryptococcal and antifungal activities potentiating activity of the studied extracts indicate their potential in the management of cryptococcosis. Further study should be considered to identify the bioactive principles against Cryptococcus neoformans.